A note on defect Mellin amplitudes - Goncalves, Vasco [UNESP]; Itsios, Georgios [UNESP] (Springer Nature, 2023)
We generalize the Mellin representation for a generic co-dimension flat defect CFT. We study the analytic structure of the Mellin amplitudes. We also compute Witten diagrams for a generic co-dimension flat defect CFT.
Keywords: Scale and Conformal Symmetries; Scattering Amplitudes